PENGARUH KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL GURU PAI TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR DI KECAMATAN MAâ€™RANG KABUPATEN PANGKEP - Hamsar, Hamsar; Yunus, Muh.; Devilla, Rego; Yahya, Muh (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
This study aims to determine and analyze 1) the influence of PAI teachers' pedagogic competence on learning achievement of elementary school students in Ma'rang District, Pangkep Regency. 2) Effect of PAI teacher professional competence on learning achievement of elementary school students in Ma'rang District, Pangkep Regency, and 3) Effect of PAI pedagogic competence and professional competence on learning achievement of elementary school students in Ma'rang District, Pangkep Regency. Pedagogic competence is a number of competencies that relate to personal abilities with all the characteristics that support the execution of tasks. Teacher's Professional Competence is a number of competencies related to professions that demand various skills in education or teacher training. This research is a type of ex-post facto research that is associative causality using quantitative analysis techniques. This research was conducted in elementary schools in the Ma'rang sub-district, Pangkep Regency. The study population was all 34 Islamic Education teachers in elementary schools in Ma'rang sub-district totaling 34 people. Samples are taken from a number of populations. In this study data on pedagogic competencies and professional competencies were obtained using a questionnaire. While the data of student learning achievement is obtained through the average grade V of PAI subjects contained in the report card that has been documented. Data management with descriptive analysis techniques and multiple linear regression. The results showed that 1) pedagogic competence of PAI teachers had a positive and significant effect on learning achievement of elementary school students in Ma'rang sub-district of Pangkep Regency by 32.71%, 2) the professional competence of PAI teachers had a positive and significant effect on elementary school students' learning achievement in Ma'rang District of Pangkep Regency was 20.43%, and 3) Pedagogic competence and professional competence of PAI teachers had a positive and significant effect on the learning achievement of elementary school students in the Ma'rang sub-district of Pangkep Regency by 31,24%.Keywords: Pedagogic Competence, Professional Competency,Â Student achievement.Â